The Role of Aceh Truth and Reconciliation Commission in Addressing Past Human Rights Violations - Juliandika, Adam; Saputra, Jummaidi; Rahmah, Siti; Nasution, Anhar; Fazzan (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2025)
The purpose of this study is to evaluate the effectiveness of KKR Aceh as a localized mechanism of transitional justice, particularly in promoting truth-seeking, victim rehabilitation, and reconciliation. Employing a normative–empirical legal approach, the research analyzes both the regulatory foundations and the practical implementation of KKR Aceh’s mandate as outlined in Law No. 11 of 2006 on the Governance of Aceh and Qanun Aceh No. 17 of 2013. Data were obtained from statutory regulations, official reports, and scholarly literature. The normative analysis focuses on the institutional design, legal legitimacy, and alignment of KKR Aceh with Indonesia’s constitutional principles and international human rights standards. Meanwhile, the empirical analysis evaluates its achievements in documenting human rights abuses, organizing public hearings, and recommending reparations for victims. The findings indicate that KKR Aceh has made substantial progress in restoring victims’ dignity and encouraging societal healing. However, its capacity remains limited due to legal, financial, and institutional challenges, including dependency on special autonomy funds and lack of coordination with national agencies. The study concludes that reinforcing KKR Aceh’s legal framework, ensuring continuous funding, and integrating reconciliation education are vital for strengthening transitional justice and sustaining peace in Aceh. [Tujuan penelitian ini adalah menilai efektivitas KKR Aceh sebagai mekanisme keadilan transisional di tingkat lokal, terutama dalam memajukan pengungkapan kebenaran, pemulihan korban, dan rekonsiliasi sosial. Dengan menggunakan pendekatan hukum normatif-empiris, penelitian ini menganalisis landasan hukum serta implementasi praktis mandat KKR Aceh sebagaimana diatur dalam Undang-Undang Nomor 11 Tahun 2006 tentang Pemerintahan Aceh dan Qanun Aceh Nomor 17 Tahun 2013. Data penelitian diperoleh dari peraturan perundang-undangan, laporan resmi, dan literatur akademik. Analisis normatif menitikberatkan pada legitimasi hukum, desain kelembagaan, serta kesesuaian KKR Aceh dengan prinsip konstitusi dan standar hak asasi manusia internasional. Sementara itu, analisis empiris menilai pencapaian lembaga ini dalam mendokumentasikan pelanggaran HAM, menyelenggarakan sidang kesaksian publik, serta memberikan rekomendasi reparasi bagi korban. Hasil penelitian menunjukkan bahwa KKR Aceh telah berkontribusi signifikan dalam memulihkan martabat korban dan memperkuat rekonsiliasi sosial. Namun, efektivitasnya masih terbatas akibat kendala hukum, keuangan, dan kelembagaan, termasuk ketergantungan pada dana otonomi khusus dan lemahnya koordinasi dengan lembaga nasional. Penelitian ini menyimpulkan bahwa penguatan dasar hukum, dukungan pendanaan berkelanjutan, dan pendidikan rekonsiliasi diperlukan untuk memperkuat keadilan transisional dan menjaga perdamaian di Aceh.]